2022
DOI: 10.29333/iji.2022.15341a
|View full text |Cite
|
Sign up to set email alerts
|

How do Students Perform a Peer Assessment?

Abstract: Peer assessment is an evaluation in which the students are assessing each other. However, do they understand what to assess, how to assess, and the objectivity of the assessment? This study aims to analyse students' ability to conduct peer assessments. The research applied a quantitative research design using questionnaire. The participant was a pre-service teacher who assessed their peers' teaching practices focused on basic teaching skills using questionnaire. The data of ten skills were obtained and analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…Reinholz (2016) defined PA as a set of activities in which individuals make judgments about the work of others. In the classroom, students are required to provide feedback or evaluation to their peers on a performance task based on a rubric or criteria that students have engaged with (Mumpuni et al, 2022). Here, students can practice helping each other and are not solely dependent on teachers to evaluate and make judgments about their work.…”
Section: Self-assessment and Peer Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Reinholz (2016) defined PA as a set of activities in which individuals make judgments about the work of others. In the classroom, students are required to provide feedback or evaluation to their peers on a performance task based on a rubric or criteria that students have engaged with (Mumpuni et al, 2022). Here, students can practice helping each other and are not solely dependent on teachers to evaluate and make judgments about their work.…”
Section: Self-assessment and Peer Assessmentmentioning
confidence: 99%
“…The benefits of PA are multiple: (1) learning gaps can be better understood when students help each other rather than receiving it from the teacher, as this improves students' status in learning (Mumpuni et al, 2022), (2) it promotes a better understanding of the criteria needed to achieve the performance goal, as students are exposed to different types of responses from peers (Reinholz, 2016), (3) they develop critical reflection skills based on others' responses (Wanner & Palmer, 2018). Schunn et al (2016) have identified two features that are critical for PA, namely that students must be able to provide sincere feedback and that teachers' fear of the social implications of honest peer review must be reduced.…”
Section: Self-assessment and Peer Assessmentmentioning
confidence: 99%
“…As stated in the study conducted by Gu (2020), there are some problems in peer assessment, such as students' hesitation to criticize their peers and students' doubts about each other's ability to make correct decisions. In addition, there are also studies showing that students score themselves lower or higher than they should be in self-assessments (Mumpuni et al, 2022;Semerci, 2011a). Therefore, it is necessary to examine in depth whether students make objective evaluations or not.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it was exemplified that the many-facet Rasch measurement model is an alternative measurement model that can be used to determine student performance. Mumpuni et al (2022), in their study aiming to analyze how peer assessment takes place, concluded that students have the ability to make peer assessments and make their assessments objectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation